PENERAPAN TOTAL PRODUCTIVE MAINTENANCE (TPM) DALAM MENINGKATKAN EFEKTIVITAS MESIN PENGEMAS DI PERUSAHAAN FARMASI - Harnawan, Christianto; Kosasih, Wilson; Kristina, Helena Juliana (Jurnal Mitra Teknik Industri, 2024)
As a company that continues to make progress and various innovations, one of the pharmaceutical companies in Jakarta continues to make continuous improvements, especially in production effectiveness and efficiency. Line 2 – CJ 3 machine is a packaging machine for liquid products which located in the black area and it has the highest running time. Based on production results and defect data for the period January 2023 to July 2023, this machine produces an average of around 23.439% defects and has various problems that affect production efficiency. The aim of this research is to determine the level of machine effectiveness using the OEE (Overall Equipment Effectiveness) method, identifying factors that influence the OEE (Overall Equipment Effectiveness) value using Six Big Losses analysis, Pareto Diagram, Fishbone Diagram, FMEA (Failure Mode and Effect Analysis), and provide suggestions for improvements and recommendations by implementing TPM (Total Product Maintenance). Based on research, the average of OEE value for Line 2 – CJ 3 machine was 47.676% and the average of reduced speed losses value was 24.999% as the bigest six big losses. The results of analysis using a fishbone diagram show that the influencing factors are man, machine, method, and material. The highest RPN (Risk Priority Number) value obtained was 294 and the lowest was 70. The improvements using TPM will be focused on Autonomous Maintenance, Planned Maintenance, and Education and Training.